Association between Grain Size and Shape and Quality Traits, and Path Analysis of Thousand Grain Weight in Iranian Bread Wheat Landraces from Different Geographic Regions - Moslem ABDIPOUR (Notulae Botanicae Horti Agrobotanici Cluj-Napoca, 2016)
Grain characteristics, particularly grain weight, grain morphology, and grain protein content (GPC), are important components of grain yield and quality in wheat. A set of 98 bread wheat landraces from different geographic regions of Iran were used across 2013-2014 and 2014-2015 to determine the phenotypic diversity and relations between thousand grain weight (TGW), grain morphology and grain quality. A high-throughput method was used to capture grain size and shape. The genotypes were significantly different (P < 0.001) for all traits which reflects the high levels of diversity. A moderate to high broad sense heritability was found for all traits and ranged between 0.68 and 0.95 for grain yield and factor from density (FFD), respectively. Significant positive correlations were observed between TGW and grain size (or shape) exception of aspect ratio (AR) and roundness. However, grain quality traits, especially GPC had significant negative correlation with TGW. Based on stepwise regression analysis by taking TGW as dependent variable, grain volume, FFD, width, perimeter and Hardness Index (HI) were recognized as the most important traits and explained more than 99.3% of total variation of TGW. The path analysis revealed that FFD has maximum direct effect on TGW followed by volume, whereas perimeter and width had relatively less direct effect on TGW. According to cluster analysis, landraces separated into 5 clusters, and cluster III and IV had the maximum and minimum average for the most traits, respectively. Our study provides new knowledge on the relations between TGW, grain morphology and grain quality in bread wheat, which may aid the improvement of wheat grain weight trait in further research.